If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 6(x + 6) + -7x Reorder the terms: 9 = 6(6 + x) + -7x 9 = (6 * 6 + x * 6) + -7x 9 = (36 + 6x) + -7x Combine like terms: 6x + -7x = -1x 9 = 36 + -1x Solving 9 = 36 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 9 + x = 36 + -1x + x Combine like terms: -1x + x = 0 9 + x = 36 + 0 9 + x = 36 Add '-9' to each side of the equation. 9 + -9 + x = 36 + -9 Combine like terms: 9 + -9 = 0 0 + x = 36 + -9 x = 36 + -9 Combine like terms: 36 + -9 = 27 x = 27 Simplifying x = 27
| h=160t-16t^2 | | -22-7x=48 | | 4(x-1)-4=2x+2(-3+x) | | u/4=-8 | | 9-0.7k=9 | | 2.37=.87h-.25 | | -5(6+5p)=136 | | -9x-36=90 | | 1+x+7-9x=-24 | | 16x-2=40x+16 | | 22=13+x | | 8a+3(-7)=3 | | -2b/13=8/3 | | a^12=5 | | 54+8x=158 | | (3x+8)=5x | | 6x-9=21+6x | | 18-3y=12 | | 2x-5=2(x-7) | | 30+3x=78 | | 6k^2-42+72=0 | | 1-121x^2= | | .4545454545h+.77777777=.22222222 | | 0.833y-0.142=0.50 | | -6m+8m=-5+2m-1 | | 6-2x-2x=26 | | 10x-60=40 | | 1.5g=-6.00 | | 14x=(11x+9) | | Ax+2=cx | | -5x+27=62 | | 4(x+5)=3(x-2)-2(x+2) |